2010
DOI: 10.4070/kcj.2010.40.10.499
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiography Patterns and the Role of the Electrocardiography Score for Risk Stratification in Acute Pulmonary Embolism

Abstract: Background and ObjectivesData on the usefulness of a combination of different electrocardiography (ECG) abnormalities in risk stratification of patients with acute pulmonary embolism (PE) are limited. We thus investigated 12-lead ECG patterns in acute PE to evaluate the role of the ECG score in risk stratification of patients with acute PE.Subjects and MethodsOne hundred twenty-five consecutive patients (63±14 years, 56 men) with acute PE who were admitted to Kyungpook National University Hospital between Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Twenty studies (4898 patients) reported data on in‐hospital mortality . Several ECG features were meta‐analyzed for this outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies (4898 patients) reported data on in‐hospital mortality . Several ECG features were meta‐analyzed for this outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Ermis et al reported median (IQR) for the Daniel score and found a significantly higher Daniel score for patients who died: 6.0 (7.0) vs 4.0 (4.0), P = 0.007. Ryu et al used a Daniel score cutoff of 12 and found that 3/38 (8%) of those in the high‐ECG score group died, whereas 12/87 (14%) of those in the low‐ECG group died ( P = 0.55).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this patient, emergent follow-up ECG in shock state showed sinus rhythm with a heart rate of 72 bpm, diffuse ST-T changes, and an S 1 Q 3 T 3 pattern. Although he did not experience sinus tachycardia, which is common in acute PE patients, 11 the diagnosis of PE could not be completely excluded because of the absence of sinus tachycardia. Nevertheless, echocardiogram showed acute RV dilatation, supporting the diagnosis of acute RV dysfunction and acute PE.…”
Section: Discussionmentioning
confidence: 86%
“…Several ECG changes have been identified in patients with pulmonary embolism (PE) 1). Precordial ST segment elevation has been previously described in patients with extensive PE 2)3).…”
mentioning
confidence: 99%